Temporary Solitaire Stent–Assisted Coiling: A Technique for the Treatment of Acutely Ruptured Wide-Neck Intracranial Aneurysms - Signorelli, F.; Gory, B.; Turjman, F. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Wide-neck intracranial aneurysms in patients with acute SAH are often challenging lesions to treat by neurosurgical and endovascular approaches. The aim of this study was to investigate the feasibility, safety, and efficacy of the use of temporary Solitaire AB stent–assisted technique with coiling for the treatment of acutely ruptured wide-neck aneurysms without perioperative antiplatelet therapy. MATERIALS AND METHODS: A retrospective review of our endovascular data base identified all patients treated in the acute phase with a temporary stent–assisted technique by use of a fully resheathable Solitaire AB stent and coiling. One-year clinical and angiographic outcomes were evaluated. RESULTS: Eight patients (5 women and 3 men; mean age, 57.5 years) with 8 ruptured wide-neck aneurysms were treated. There were 3 complications without clinical impact. Postoperative complete occlusion was achieved in 5 aneurysms, and 3 had a neck remnant. Three patients had an mRS score of 0, and 1 an mRS score of 3. Among the 4 patients admitted with a World Federation of Neurological Societies grade of V, 1 died, 1 improved to an mRS score of 1, and the other 2 achieved mRS scores of 4 and 5. Five had a stable occlusion, and 2 of the 3 incompletely occluded aneurysms underwent recanalization. CONCLUSIONS: In this small series, temporary placement of the Solitaire AB stent during coiling was a feasible and effective treatment for acutely ruptured wide-neck aneurysms. This technique, avoiding the need for perioperative antiplatelet therapy, could be a valuable option for the treatment of such lesions when the balloon remodeling technique is either not an option or unsuccessful. EVDexternal ventricular drainSACstent-assisted coilingWFNSWorld Federation of Neurological Societies